2020
DOI: 10.3390/ani10112151
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Toxic Elements in Bone and Bone Marrow of Deer Living in Various Ecosystems. A Case Study of Farmed and Wild-Living Deer

Abstract: The aim of the study was to determine the concentrations of toxic elements accumulated in the bone marrow and bones (Cervus elaphus). The studies were carried out on two groups of young stags: farmed (n = 6) and wild (n = 9). Their body weights were measured and bone and bone marrow samples were collected. The concentrations of toxic elements were analyzed using the inductively coupled plasma mass spectrometry technique. The mean aluminum content in the bone marrow and bones of the farmed animals was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…When comparing soft tissues, higher concentrations of Ca, P, Mg, Cr, Zn, Se, Al, Ba and Ni in bone marrow than in plasma were demonstrated. This research also confirms our previous study on the translocation of minerals within the body and depending on the consumed food and metabolic changes [ 8 , 15 ] due to the fact that blood does not accumulate minerals but only transports them and reflects their amount at a given time. Blood is a tissue with a high renewal rate due to the physiologically short life span of cells in the circulation.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…When comparing soft tissues, higher concentrations of Ca, P, Mg, Cr, Zn, Se, Al, Ba and Ni in bone marrow than in plasma were demonstrated. This research also confirms our previous study on the translocation of minerals within the body and depending on the consumed food and metabolic changes [ 8 , 15 ] due to the fact that blood does not accumulate minerals but only transports them and reflects their amount at a given time. Blood is a tissue with a high renewal rate due to the physiologically short life span of cells in the circulation.…”
Section: Discussionsupporting
confidence: 91%
“…In the studies of Hassan et al [ 16 ] on the bone marrow of reindeer, evidence of Cd, Pb, and As was demonstrated, and in the presented studies in fallow deer, the content of these elements was below the detection level. In the bone marrow of farmed and wild red deer living in the same area [ 8 ], higher concentrations of As, Ba, Pb and Ni were found only in wild animals (0.008 mg/kg, 0.969 mg/kg, 0.003 mg/kg, 0.042 mg/kg, respectively), while lower Al levels (2.638 mg/kg) and the same levels of Be, Cd, Sb (<LOD) and Ni (0.014 mg/kg) were found in farmed red deer compared to with fallow deer. The described differences in the concentrations of individual bulk, trace and toxic elements may result from differences between species, but they may also be caused by the different ages of the tested animals and the potential for assimilation of individual elements resulting from individual characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations